Reading the book of nature how eight best sellers reconnected Christianity and the sciences on the eve of the Victorian age - Topham, Jonathan R. (The University of Chicago Press, 2022)
"When Darwin returned to Britain from the Beagle voyage in 1836, the most talked-about scientific books were the Bridgewater Treatises. This series of eight books was funded by a bequest of the last Earl of Bridgewater, and they were authored by leading men of science, appointed by the President of the Royal Society, and intended to explore "the power, wisdom, and goodness of God, as manifested in the creation." Securing public attention beyond all expectations, the series gave Darwin's generation a range of approaches to one of the great questions of the age: how to incorporate the newly emerging disciplinary sciences into Britain's overwhelmingly Christian culture. Drawing on a wealth of archival and published sources, including many unexplored by historians, Jonathan R. Topham examines how and to what extent the series contributed to a sense of congruence between Christianity and the sciences in the generation before the infamous Victorian "conflict between science and religion." He does so by drawing on the distinctive insights of book history, using close attention to the production, circulation, and use of the books to open up new perspectives not only on aspects of early Victorian science but also on the whole subject of science and religion. Its innovative focus on practices of authorship, publishing, and reading helps us to understand the everyday considerations and activities through which the religious culture of early Victorian science was fashioned. And in doing so, Reading the Book of Nature powerfully reimagines the world in which a young Charles Darwin learned how to think about the implications of his theory"--
Literaturverzeichnis Seite [511]-553. - Index
Keywords: Egerton, Francis Henry of -- 1756-1829; Geschichte 1833-1836; Natürliche Theologie; Monografische Reihe; Gottesfrage; Naturwissenschaften; Großbritannien; Bridgewater treatises on the power, wisdom, and goodness of God, as manifested in the creation; Religion and science / England / History / 19th century; Books and reading / England / History / 19th century; Religion et sciences / Angleterre / Histoire / 19e siècle; Livres et lecture / Angleterre / Histoire / 19e siècle; Books and reading; Religion and science; England; 1800-1899; History